Design and Management of Stray Light for Compact Final Optics Assembly on the High Energy Laser System - Zhu, Deyan; Chen, Yang; Li, Ping; Feng, Bin; Pang, Yajun (International Journal of Optics, 2021)
In this study, a model is proposed to design and manage the stray light of a compact final optics assembly (FOA) for a high energy laser system. Based on the method we proposed, the high-order stray light can be managed to optimizing the position and angle of the optical elements. A light trap is designed to manage the first-order stray light with high fluence. Applying the method, we provide an experimental demonstration to designing a compact FOA. By comparing the cleaning results with no management testing result, it proves that using the above design and management, it can achieve the great improvement of cleanliness from ISO Class 5 to Class 3, which is significant to improve the output capability of the high energy laser system. In addition, we also verify the stray light by an optical field paper. It demonstrates that the field characteristics and position calculation of stray light are reliable.